Aging effects on the encoding/retrieval flip in associative memory: fMRI evidence from incidental contingency learning - Schneider, Else; Rajkovic, Marko; Krug, Rudolf; Caviezel, Marco P.; Reichert, Carolin F.; Bieri, Oliver; Schmidt, André; Borgwardt, Stefan; Leyhe, Thomas; Linnemann, Christoph; Brühl, Annette B.; Lang, Undine E.; et al. (Frontiers in Aging Neuroscience, 2024)
Introduction Associative memory is arguably the most basic memory function and therein constitutes the foundation of all episodic and semantic memory processes. At the same time, the decline of associative memory represents a core feature of age-related cognitive decline in both, healthy and pathological (i.e., dementia-related) aging. The neural mechanisms underlying age-related impairments in associative memory are still not fully understood, especially regarding incidental (i.e., non-intentional) learning. Methods We investigated the impact of age on the incidental learning and memory retrieval of face-name combinations in a total sample of 46 young (N = 23; mean age = 23.39 years) and elderly (N = 22, mean age = 69.05 years) participants. More specifically, particular interest was placed in age-related changes in encoding/retrieval (E/R) flips, which denote a neural antagonism of opposed activation patterns in the same brain region during memory encoding and retrieval, which were assessed using fMRI. Results According to our hypothesis, the results showed a significant age-related decline in the retrieval performance in the old group. Additionally, at the neural level, we discovered an abolished E/R flip in the right anterior insula and a joint but reduced E/R flip activation magnitude in the posterior middle cingulate cortex in older subjects. Discussion In conclusion, the present findings suggest that the impaired neural modulation of the E/R flip in the right aIC might be a sensitive marker in the early detection of neural aging.